A Giant Ovarian Cystadenoma in A 20-Year-Old Nulliparous Woman: A Case Report - Pramana, Cipta; Almarjan, Lulu; Mahaputera, Pramadio; Wicaksono, Satrio Adi; Respati, Giri; Wahyudi, Firdaus; Hadi, Cahyono (Frontiers in Surgery, 2022)
Giant ovarian cyst itself is defined as a cyst > 10 cm in diameter from radiological- examination or the size of the cyst exceeds the umbilicus. Extra-large benign and malignant cysts of the ovary are uncommon and involve diagnostic and management challenges. We present the case of a 20-year-old nulliparous woman who was referred to our center with complaints of abdominal pain and heavy breathing. She benefited from a salphingo-oophorectomy laparotomy procedure. Benign and malignant gynecologic and non-gynecologic etiologies are included in the differential diagnosis of an abdominal mass. Because of the infrequent occurrence or absence of distinctive clinical presentation of the giant ovarian cyst, accurate preoperative diagnosis is challenging.